Antioxidant Isosantosimol from Garcinia griffithii Stem Bark - Elfita Elfita; Supriyatna Supriyatna; Husein H. Bahti; Dachariyanus Dachariyanus (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2008)
A polyisoprenylated benzophenone, isosantosimol had been isolated from the stem bark of Garcinia griffithii T. Anders. The structure of these compound was determined on the basis of spectroscopic data including UV, IR, 1H NMR, 13C NMR, HMQC, HMBC and COSY, as well as by direct comparison with those of reported data. The antioxidant activity of this compound was observed using radical scavenging 1,1-diphenyl-2-picryl hydrazyl (DPPH) model systems.